Light & Shadow learn to Paint Step by Step - Swimm, Tom (Laguna Hills, Calif Walter Foster Pub, 2009)
Capturing the play of light - depicting time of day - choosing shadow - painting a nighhime scene
Arts(Drawing)
Cover title
1 2 13
Keywords: Acrylic painting -- Technique; Drawing -- Technique; Drawing materials